BALINESE CULTURE AND REPEAT VISITORS TO BALI - I Ketut Sutama; I Gede Mudana; I Ketut Astawa (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2017)
The intention to revisit a destination usually happens during tourists’ first visit. The decision begins when tourists’ expectations meet the reality in the destination visited, moreover it exceeds the expectations. The main purpose of tourists visit a destination is one of the following: holiday, visiting friends and relatives (VFR), business, education, sports and health, but it may be a combination of them, such as holiday and VFR, holiday and business, etc. In terms of holiday it may include relax, learn and enjoy arts and culture, enjoy nature beauty, and honeymoon. The purpose of this study was to know how Balinese culture affect international tourists revisit Bali. Since Bali is known as cultural tourist destination it is worth to know more deeply. In regard with this study it was found that the number of visit by international repeating-tourists to Bali was as follows: 6 to 9 visits (28%), more than 25 visits (25%), 3 to 5 visits (25%), 14 to 17 visits (10%), 18 to 21 visits (7%), and 10 to 13 visits (5%). Three most reasons repeaters revisited Bali were friendly people, ‘love Bali’, and the charm of Bali. Their reasons were influenced by a number of factors including holiday (65%), followed by business (22.5%), VFR (7.5%), and others (5%). From this fact it may say that Bali is still considered best destination for holiday. Nine most preferable activities done by revisiting international tourists during in Bali were relax (15%), interact with local people (14%), beach activities (13%), adventure activities (11%), sightseeing (10%), learning local culture (9%), attending temple ceremony (8%), enjoying night life (7%), and business (6%). In terms of revisiting behavior, connection with a visited destination is considered significant by experts. Connection in this case may be tangible and intangible. Tangible connection may include business and social networks, while intangible connection is seen through psychological aspect. In this study attachment theory was used to examine the connection between repeaters and Bali as a tourist destination. It was found that most repeaters had strong connection to Bali, mostly affected by friendly people of Bali (social connection), uniqueness of culture (cultural connection), and natural beauty or the charm of Bali (place connection). Further study is important to conduct to know more about how each connection influence each other.